Monoclonal antibodies effectively potentiate complement activation and phagocytosis of Staphylococcus epidermidis in neonatal human plasma - de Vor, Lisanne; Beudeker, Coco R.; Flier, Anne; Scheepmaker, Lisette M.; Aerts, Piet C.; Vijlbrief, Daniel C.; Bekker, Mireille N.; Beurskens, Frank J.; van Kessel, Kok P. M.; de Haas, Carla J. C.; Rooijakkers, Suzan H. M.; van der Flier, Michiel (Frontiers in Immunology, 2022)
Central line associated bloodstream infections (CLABSI) with Staphylococcus epidermidis are a major cause of morbidity in neonates, who have an increased risk of infection because of their immature immune system. As especially preterm neonates suffer from antibody deficiency, clinical studies into preventive therapies have thus far focused on antibody supplementation with pooled intravenous immunoglobulins from healthy donors (IVIG) but with little success. Here we study the potential of monoclonal antibodies (mAbs) against S. epidermidis to induce phagocytic killing by human neutrophils. Nine different mAbs recognizing Staphylococcal surface components were cloned and expressed as human IgG1s. In binding assays, clones rF1, CR5133 and CR6453 showed the strongest binding to S. epidermidis ATCC14990 and CR5133 and CR6453 bound the majority of clinical isolates from neonatal sepsis (19 out of 20). To study the immune-activating potential of rF1, CR5133 and CR6453, bacteria were opsonized with mAbs in the presence or absence of complement. We observed that activation of the complement system is essential to induce efficient phagocytosis of S. epidermidis. Complement activation and phagocytic killing could be enhanced by Fc-mutations that improve IgG1 hexamerization on cellular surfaces. Finally, we studied the ability of the mAbs to activate complement in r-Hirudin neonatal plasma conditions. We show that classical pathway complement activity in plasma isolated from neonatal cord blood is comparable to adult levels. Furthermore, mAbs could greatly enhance phagocytosis of S. epidermidis in neonatal plasma. Altogether, our findings provide insights that are crucial for optimizing anti-S. epidermidis mAbs as prophylactic agents for neonatal CLABSI.